Analisis indikator keberkahan berzakat bagi muzaki di jalur Joglosemar - Ahmad Mifdlol Muthohar (State Institute of Islamic Studies (IAIN) Salatiga, 2017)
The purpose of this study is to find out the concept of blessing in giving zakat according to Islamic teaching and to deepen its indicators felt by muzaki. Research method used in this study is qualitative approach. Technique of collecting data is documentation, observation and interview. The interview was conducted twice. The first step was done to 396 respondents, and then it’s continued to the second step with 20 different respondents. Sampling technique used in this study is purposive random sampling. Research findings showed that 98% of muzaki stated that they felt the existence of blessing in giving zakat, and according to them the highest blessing is inner peace; however when high percentage is correlated to the tendency of giving zakat to zakat institution, the result is not correlated. In addition to those mentioned, muzaki felt religious experiences related to blessing after they paid zakat. The highest blessings they felt most are: inner peace, easy of business, calm feeling, effective property, and far from harmful things.